Exploring gender, tenure security, and landscape governance approaches and findings: Lessons from eight years of research - Kristjanson, Patricia; Larson, Anne; Meinzen-Dick, Ruth S. (International Food Policy Research Institute, 2021)
This brief synthesizes approaches and findings from gender research conducted by the CGIAR Program on Policy, Institutions, and Markets (PIM). The focus of this work is the governance of natural resources and and institutions for improved natural resources management. This body of research analyzes how tenure security affects sustainable management and how individuals, groups, and communities govern land, water, fish stocks, and forests. An important focus of this work involves the following questions: (1) who has what rights with respect to these resources (particularly for women and members of marginalized groups), (2) what are their roles in managing natural resources, and (3) what livelihood benefits do they receive? Without a contextualized understanding of these questions, policies and practices can inadvertently exclude women, reinforce historical practices of gender injustice, or introduce new inequalities that worsen natural resource management and poverty.